Comparison of the incidence of skin cancers in patients on dialysis and after kidney transplantation - Sułowicz, Joanna; Wojas-Pelc, Anna; Ignacak, Ewa; Krzanowska, Katarzyna; Kuźniewski, Marek; Sułowicz, Władysław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Kidney transplant (KTx) patients on immunosuppressive therapy are predisposed to the development of infections and cancers. Aim : To compare the incidence and type of malignant skin lesions in kidney transplant patients and the dialyzed population based on the initiated dermatologic screening. Material and methods : The study included 598 patients: 486 kidney transplant recipients and 112 patients on maintenance dialysis. All the patients underwent dermatological examination. Only histologically confirmed cancers were included in this study. Age, gender and immunosuppressive therapy administration were also considered. Patients were followed up by a dermatologist for a period of 5 years. Results : Fifty-eight skin cancers; 39 basal cell carcinomas (BCC), 13 squamous cell carcinomas (SCC), 1 Bowen disease, 2 Kaposi sarcoma, 1 malignant melanoma, 1 Merkel cell carcinoma, and 1 fibrosarcoma protuberans were diagnosed in 30 (6.2%) kidney transplant patients, and 8 lesions (7 BCC and 1 SCC) were found in 4 (3.6%) patients on dialysis. Conclusions : The initiated dermatologic screening program indicates that the risk of skin cancer incidence in post kidney transplant patients receiving immunosuppressive therapy was significantly higher than in patients on dialysis.